Synthesis, biological and medicinal impacts of metallodrugs: A study - Emranul Kabir; M.R.O. Khan Noyon; Md. Amjad Hossain (Results in Chemistry, 2023)
The behavior of metals and metallodrugs in biological systems affects the setup of therapeutic strategies with a distinct mode of action and new knowledge of clinically-proven drugs. Metals also have essential chemical roles in foods and therapies. Despite the abundance of newly synthesized molecules, metallodrugs have been the focus of several pharmaceutical investigations, but their distinct modes of action are primarily unknown or incompletely understood. Scientists now have new tools to understand how metallodrugs can be effective against various diseases because of the ongoing development of effective and sensitive molecular biology and chemistry techniques. Research on employing metals in medicine focuses on metal complexes to detect diseases and specially designed ligands to sense biologically occurring metal ions. This study focuses on current findings on the metallodrugs’ syntheses, their therapeutic mode of action, and how the ligands can modify their pharmacological and physicochemical features.